2018
DOI: 10.1093/geront/gny005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Autonomy, Relatedness, and Competence With the Well-being of Nursing Home Residents

Abstract: These results confirm that all three basic psychological needs are important for nursing home residents' well-being, with autonomy having the strongest and most consistent relationship to their well-being. Additionally, high satisfaction of one need does not compensate for low satisfaction of another. Supporting residents' needs for autonomy, relatedness, and competence should, therefore, have a central role in nursing home culture-change interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…We observed that, regardless of whether or not they involved gardening/horticulture activities, interventions were more likely to be effective when they afforded: 1) shared/group experiences; 2) acquiring knowledge and learning skills; and/or, 3) opportunities to have control/autonomy, provide care, or be responsible for nature. Each of these factors: social interaction (Bassuk, 1999;Graney, 1975;Mendes de Leon, Glass, & Berkman, 2003), lifelong learning (Narushima, Liu, & Diestelkamp, 2013, and having responsibility/autonomy (Kloos, Trompetter, Bohlmeijer, & Westerhof, 2018;Langer & Rodin, 1976), have been reported to benefit older adults' wellbeing, in terms of ADL (Mendes de Leon et al, 2003), happiness (Graney, 1975), cognition (Bassuk, 1999), depression (Kloos et al, 2018), general psychological wellbeing (Kloos et al, 2018;Narushima et al, 2013), general overall health (Langer & Rodin, 1976), and life satisfaction (Kloos et al, 2018), i.e. similar outcomes to those reported in this review.…”
Section: Identifying Key Features Of Stronger Interventionssupporting
confidence: 74%
“…We observed that, regardless of whether or not they involved gardening/horticulture activities, interventions were more likely to be effective when they afforded: 1) shared/group experiences; 2) acquiring knowledge and learning skills; and/or, 3) opportunities to have control/autonomy, provide care, or be responsible for nature. Each of these factors: social interaction (Bassuk, 1999;Graney, 1975;Mendes de Leon, Glass, & Berkman, 2003), lifelong learning (Narushima, Liu, & Diestelkamp, 2013, and having responsibility/autonomy (Kloos, Trompetter, Bohlmeijer, & Westerhof, 2018;Langer & Rodin, 1976), have been reported to benefit older adults' wellbeing, in terms of ADL (Mendes de Leon et al, 2003), happiness (Graney, 1975), cognition (Bassuk, 1999), depression (Kloos et al, 2018), general psychological wellbeing (Kloos et al, 2018;Narushima et al, 2013), general overall health (Langer & Rodin, 1976), and life satisfaction (Kloos et al, 2018), i.e. similar outcomes to those reported in this review.…”
Section: Identifying Key Features Of Stronger Interventionssupporting
confidence: 74%
“…SDT outlines three basic psychological needs-autonomy, competence, and relatedness-and postulates that an individual's well-being and functioning are dependent upon the satisfaction of these needs. Evidence from numerous studies has shown that satisfaction of these basic psychological needs is vital for peoples' well-being in various contexts and cultures (e.g., Chen et al 2015;Church et al 2013;Kloos et al 2018;Ng et al 2012;Van den Broeck et al 2016). The degree of one's need satisfaction is in turn affected by various individual, environmental, and social factors (Ryan and Deci 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in their reflection, staff co‐researchers related many of the ‘less obvious’ restrictions (specifically concerning freedom of choice) to routine (habit) and institutionalization. Living in a group can provide residents with an essential sense of belonging and emotional security (Custers et al, 2011; Kloos et al, 2019), yet nursing homes and nursing staff may need to increase their awareness of restrictive daily routines that are lurking in institutionalized settings and may lead to a lack of attention to individual preferences and to more passive residents.…”
Section: Discussionmentioning
confidence: 99%